A Quantum Hamiltonian Identification Algorithm: Computational Complexity and Error Analysis - Yuanlong Wang; Daoyi Dong; Bo Qi; Jun Zhang; Petersen, Ian R.; Yonezawa, Hidehiro (IEEE transactions on automatic control, 2018)
Quantum Hamiltonian identification (QHI) is important for characterizing the dynamics of quantum systems, calibrating quantum devices, and achieving precise quantum control. In this paper, an effective two-step optimization (TSO) QHI algorithm is developed within the framework of quantum process tomography. In the identification method, different probe states are input into quantum systems and the output states are estimated using the quantum state tomography protocol via linear regression estimation. The time-independent system Hamiltonian is reconstructed based on the experimental data for the output states. The Hamiltonian identification method has computational complexity O(d 6 ), where d is the dimension of the system Hamiltonian. An error upper bound O( d 3 /√N ) is also established, where N is the resource number for the tomography of each output state, and several numerical examples demonstrate the effectiveness of the proposed TSO Hamiltonian identification method.